Efektivitas penerimaan Pajak Penghasilan final UMKM pada KPP Pratama Malang Utara - Maria Da Rosalina Yawa; Fitriana Santi; Hanjar Ikrima Nanda (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2021)
This study aims to determine the level of effectiveness of the final income of MSMEs (Micro, Small and Medium Enterprises). Methods of data collection with the method of documentation. The data analysis technique used is descriptive quantitative. The results of the study show that for the last 5 years KPP Pratama North Malang has not achieved the realization of tax revenue from the target that has been set. This is influenced by the fact that taxpayers are still not aware of the obligation to pay taxes.